2016
DOI: 10.1021/jacs.6b00345
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structures of Hauser Base iPr2NMgCl and Turbo-Hauser Base iPr2NMgCl·LiCl in THF and the Influence of LiCl on the Schlenk-Equilibrium

Abstract: Grignard reagents that are at the simplest level described as "RMgX" (where R is an organic substituent and X a halide) are one of the most widely utilized classes of synthetic reagents. Lately, especially Grignard reagents with amido ligands of the type R1R2NMgX, so-called Hauser bases, and their Turbo analogue R1R2NMgX·LiCl play an outranging role in modern synthetic chemistry. However, because of their complex solution behavior, where Schlenk-type equilibria are involved, very little is known about their st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
75
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(79 citation statements)
references
References 102 publications
4
75
0
Order By: Relevance
“…Our investigations confirm that lithium chloride indeed co‐coordinates to the magnesium amides in solution as observed in the Turbo‐Hauser base 2 . A detectable population of the solvent separated lithium cation Li2 can also be excluded for Turbo‐Hauser base 1 (MW calcd =295 g mol −1 , MW det =387 g mol −1 , MW err =−31 %).…”
Section: Figuresupporting
confidence: 77%
See 3 more Smart Citations
“…Our investigations confirm that lithium chloride indeed co‐coordinates to the magnesium amides in solution as observed in the Turbo‐Hauser base 2 . A detectable population of the solvent separated lithium cation Li2 can also be excluded for Turbo‐Hauser base 1 (MW calcd =295 g mol −1 , MW det =387 g mol −1 , MW err =−31 %).…”
Section: Figuresupporting
confidence: 77%
“…At least, in the solid state the Turbo‐Hauser bases TMPMgCl ⋅ LiCl 1 C and DAMgCl ⋅ LiCl 2 A (Figure b) supported the existence of a contact ion pair (CIP). Recently, we showed that redissolved crystals of 2 A do not form SSIPs in THF solution either . Instead, the dimeric crystal structure 2 A equilibrates with its monomeric counterpart 2 C at room temperature.…”
Section: Figurementioning
confidence: 98%
See 2 more Smart Citations
“…Starting materials were purchased commercially and were used as received, unless stated otherwise. ( i Pr) 2 NMgCl and KC 8 were synthesized according to literature procedures . 1 H‐ and 13 C NMR spectra were recorded with a Bruker Avance 300 or 400 MHz spectrometer and are referenced to the residual proton signal of the deuterated solvent .…”
Section: Methodsmentioning
confidence: 99%